Tango along the Canadian–American Border in the 1920s. Issue 2 (3rd April 2018) - Willis, John
ABSTRACT: From 1920 until 1933, American Prohibition altered relations between Canada and the United States. Prohibition contributed to the advent of an underground liquor economy predicated on a pattern of widespread cross-border smuggling and forced the agencies overseeing the border to bring the situation under control. I examine Canadian and American customs organizations with especial focus on the Québec–New York State and Vermont border. The pressure on Canada's Customs and Excise Department was strong. The US government wanted to ban Canadian liquor imports. Members of the Canadian liquor cartel wanted the exact reverse. The Canadian department, sensitive to the prosperity of the unprecedented rise in Canada's liquor production, was overwhelmed by the scope of illegal liquor activities. Moreover, under the influence of the liquor economy, Customs and Excise experienced corruption within its ranks. The period of prohibition was one of tension, along the border, between police and smugglers, and between countries with different interests and priorities. It is a significant episode in an ongoing relationship (or dance) between close partners.